2020
DOI: 10.3389/fmicb.2020.00651
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Marseillevirus Transcriptome Reveals Temporal Gene Expression Profile and Host Transcriptional Shift

Abstract: Marseilleviruses comprise a family of large double-stranded DNA viruses belonging to the proposed order "Megavirales." These viruses have a circular genome of ∼370 kbp, coding hundreds of genes. Over a half of their genes are associated with AT-rich putative promoter motifs, which have been demonstrated to be important for gene regulation. However, the transcriptional profile of Marseilleviruses is currently unknown. Here we used RNA sequencing technology to get a general transcriptional profile of Marseillevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 67 publications
(94 reference statements)
6
31
0
Order By: Relevance
“…We next focused on the marseillevirus virion-associated protein-coding genes to check whether they were expressed in a time-dependent manner. Confirming the results previously obtained [18], we found an enrichment in virion-associated genes in the late expression class. In addition, we also found that marseillevirus genes orthologous to melbournevirus and noumeavirus virion-associated genes were enriched in that category ( Figure S5).…”
Section: Biaised Distribution Of Virion-associated Proteins and Late-supporting
confidence: 91%
See 4 more Smart Citations
“…We next focused on the marseillevirus virion-associated protein-coding genes to check whether they were expressed in a time-dependent manner. Confirming the results previously obtained [18], we found an enrichment in virion-associated genes in the late expression class. In addition, we also found that marseillevirus genes orthologous to melbournevirus and noumeavirus virion-associated genes were enriched in that category ( Figure S5).…”
Section: Biaised Distribution Of Virion-associated Proteins and Late-supporting
confidence: 91%
“…Starting from the raw sequence data, we mapped the reads to the A. castellanii and marseillevirus genomes, and computed a normalized expression value for each gene (see Materials and Methods). As previously observed [18], we found the marseillevirus' genes expressions to be clustered into three main classes: early, intermediate and late (Figure S5). Early genes are expressed from the beginning of the cycle, with a peak of transcriptional activity between 1 h pi and 2 h pi, intermediate genes are mostly expressed between 1 h pi and 4 h pi, and late genes from 4 h pi until the end of the cycle.…”
Section: Biaised Distribution Of Virion-associated Proteins and Late-supporting
confidence: 83%
See 3 more Smart Citations